2016
DOI: 10.1093/chemse/bjw077
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Cytosolic ClConcentrations in Dendritic Knobs of Mouse Vomeronasal Sensory Neurons

Abstract: In rodents, the vomeronasal system controls social and sexual behavior. However, several mechanistic aspects of sensory signaling in the vomeronasal organ remain unclear. Here, we investigate the biophysical basis of a recently proposed vomeronasal signal transduction component-a Ca 2+ -activated Cl − current. As the physiological role of such a current is a direct function of the Cl − equilibrium potential, we determined the intracellular Cl − concentration in dendritic knobs of vomeronasal neurons. Quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 76 publications
0
13
2
Order By: Relevance
“…Although we found Ano2 B⌬4 transcripts in the VNO, we also detected mRNA that included exon 4 and thus encodes functional Ano2 channels. We found no evidence for the recently proposed scenario (15) in which functional isoforms of Ano2 are only expressed in supporting cells because we did not detect Ano2 in those cells. Because we cannot exclude that Ano2 mediates minor chloride currents in VSNs, we investigated the physiological role of CaCCs in the VNO using mice lacking both Ano1 and Ano2 in VSNs (⌬(Ano1 olf /Ano2) mice).…”
Section: Ca 2؉ -Activated CL ؊ Currents In the Vomeronasal Organcontrasting
confidence: 99%
See 2 more Smart Citations
“…Although we found Ano2 B⌬4 transcripts in the VNO, we also detected mRNA that included exon 4 and thus encodes functional Ano2 channels. We found no evidence for the recently proposed scenario (15) in which functional isoforms of Ano2 are only expressed in supporting cells because we did not detect Ano2 in those cells. Because we cannot exclude that Ano2 mediates minor chloride currents in VSNs, we investigated the physiological role of CaCCs in the VNO using mice lacking both Ano1 and Ano2 in VSNs (⌬(Ano1 olf /Ano2) mice).…”
Section: Ca 2؉ -Activated CL ؊ Currents In the Vomeronasal Organcontrasting
confidence: 99%
“…These data do not rule out an additional expression in supporting sustentacular cells of the VNE as suggested previously (15). However, such an expression is excluded for Ano1 because neuronal-specific OMP-Cre-mediated Ano1 knockout completely abolished Ano1 immunoreactivity of VNO microvilli.…”
Section: Ano1 and Ano2 Co-localization In Microvilli Of Vsnscontrasting
confidence: 61%
See 1 more Smart Citation
“…Among others, Ca 2+ -FLIM revealed globally increased calcium concentrations in astrocytes close to amyloid plaques in mouse models of Alzheimer's disease (Kuchibhotla et al, 2009) or demonstrated different resting calcium levels along dendrites of hippocampal neurons in rat brain tissue (Zheng et al, 2015). FLIM of ion indicators has also been employed for determination of intracellular chloride concentrations, e.g., in olfactory epithelia (Kaneko et al, 2004), dorsal root ganglia of rodents (Gilbert et al, 2007), cockroach salivary acinar cells (Lahn et al, 2011), cells of the mouse vomeronasal organ (Untiet et al, 2016), or acute slices of mouse brain (Untiet et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…So far, glial [Cl − ] int has been determined in cultured astrocytes with results varying between 29–46 mM (Bekar and Walz, ; Bevensee et al, ; Kettenmann et al, ; Kimelberg, ; Smith et al, ; Walz and Mukerji, ). Here we used fluorescence lifetime imaging microscopy (FLIM) with the chloride‐sensitive dye MQAE (Gensch et al, ; Kovalchuk and Garaschuk, ; Marandi et al, ; Untiet et al, ) in acute cerebellar slices to determine the [Cl − ] int in Bergmann glial cells at different stages of postnatal development and to study pathways involved in its regulation. We found that anion channels associated with two glial glutamate transporters, excitatory amino acid transporter 1 and 2 (EAAT1 and EAAT2), modify the resting [Cl − ] int in adult wild type (WT) glia and dynamically modulate these values in response to cerebellar neuronal activity.…”
Section: Introductionmentioning
confidence: 99%